The effectiveness of a distance learning application in light of the spread of the COVID-19 pandemic from the point of view of teachers in the Qasr District - Al-Omarin, Nusaiba Ibrahim (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the effectiveness of the application of distance learning in light of the spread of the COVID-19 pandemic from the point of view of teachers in the Qasr District, and to reveal the difference in their views towards the effectiveness of the application of distance learning in light of the spread of the COVID-19 pandemic, according to the variables (gender, educational qualification)., Years of Experience). To achieve its objectives, the study used the sample social survey method, and the use of the questionnaire tool to collect data. The study sample consisted of 192 male and female teachers selected from the basic schools in the Qasr District. The questionnaire was applied via websites to the target group for the study. The results showed that the general level of effectiveness of the distance learning application in light of the spread of the COVID-19 pandemic from the point of view of teachers in the Qasr District came at a high level, as the general level of the answers of the study sample reached (3.818), and the results showed that there were no statistically significant differences between the average The responses of the study sample members towards the effectiveness of the distance learning application in light of the spread of the COVID-19 pandemic from the point of view of teachers in the Qasr District, according to the variable of gender and educational qualification, while the results showed that there were statistically significant differences according to the variable number of years of experience and in favor of the study sample members of the long experience category(10 years and over).